The integration role of governmental information disclosure platform: An evolutionary game analysis of corporate environmental monitoring data fraud. Issue 5 (13th August 2019) - Peng, Jing; Tu, Guoping; Liu, Yanhong; Zhang, Hao; Leng, Bibing
Abstract : Purpose: The purpose of this paper is to provide a feasible scheme for local governments to regulate corporate environmental data fraud and to discuss whether the influence of the construction of online information disclosure platform on the environmental behavior of enterprises is better than the offline spot check. Design/methodology/approach: Under the background of changing environmental fees into taxes in China, this paper conducts evolutionary game analysis between local governments and enterprises in view of the existing problem of environmental data fraud. Furthermore, through the introduction of government information disclosure platform, this paper discusses the impact of the integration of direct government regulation and indirect public concern regulation on the evolution of environmental behavior of both sides. Finally, the evolutionary game is simulated by adopting system dynamics to analyses the implementation effect of different cases on the game process and game equilibrium. Findings: The results showed that the introduction of information disclosure platform mechanism can effectively suppress the fluctuations existing in the game play and stabilize the game. Moreover, it is worth noting that the regulatory effect of local governments investing part of the monitoring cost in the construction of online information platform is proved to be better than that of putting all the monitoring cost into offline investigation. While optimizing the monitoring cost allocation, the local government still needs to attach great importance to organically combine the attention of the public and media with the governmental official platform. Practical implications: The obtained results confirm that the proposed model can assist local government in refining the effects of their environmental regulatory decisions, especially in the case of corporate data fraud under environmental tax enforcement. Originality/value: Previous literature only suggested that local governments should reduce the cost of supervision to change the corporate behavior to a better direction, but no further in-depth study. Thus, this study fills the gap by discussing the positive transformation effect of local government cost allocation scheme on corporate environmental behavior.